FEATURES OF SYSTEM ANALYSIS IN THE DEVELOPMENT OF PEDAGOGICAL COMPETENCE OF COMPUTER SCIENCE TEACHERS - R. G‘.Tugalov, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
Today, methodological improvement and development of professional competence of teachers is one of the important issues of the educational process. The article reveals the basic concepts, essence, role, significance and features of system analysis in the development of pedagogical competence of computer science teachers.